Deterioration mechanism of hydrothermal aging on the properties of carbon fiber/epoxy composites in various media. (March 2023) - Fang, Wu; Guo, Wenjian
This study examined the hydrothermal aging mechanism of carbon fiber reinforced epoxy resin (CF/EP) composites in acidic, alkaline, salt solution, and deionized water (marked as Ac-CF/EP, Al-CF/EP, Sa-CF/EP, and De-CF/EP). The water absorption of carbon fiber reinforced epoxy resin composites followed a two-step process for all four aging mediums, including an initial Fickian diffusion and a subsequent long-term deterioration response. The carbon fiber reinforced epoxy resin composites were degraded more easily in a weak acidic solution due to the degradation of secondary amines and ether bond in an EP molecular chain, which was even degraded into methyl, ethyl, isopropyl, and bisphenol-A monomers. Long-term hydrothermal aging led to significant degradation of the CF/EP composites in all four mediums, the shear strength of the aged composites from small to large was Ac-CF/EP < Al-CF/EP < De-CF/EP < Sa-CF/EP < raw carbon fiber reinforced epoxy resin, which reduced the bending strength by 38.1%, 31.0%, 20.9%, and 11.5%, respectively, compared to the raw carbon fiber reinforced epoxy resin composites. The degradation of the EP matrix and irreversible interface damage caused by hydrothermal aging were considered the main reasons for the degraded mechanical properties of the carbon fiber reinforced epoxy resin composites. It is strongly recommended to apply a protective film on the surface of carbon fiber reinforced epoxy resin composites to reduce the possibility of interaction with humid air.